College Students with ADHD and LD: Effects of Support Services on Academic Performance - DuPaul, George J.; Dahlstrom-Hakki, Ibrahim; Gormley, Matthew J.; Fu, Qiong; Pinho, Trevor D.; Banerjee, Manju (Learning disabilities research and practice, 2017)
Two relatively common disabilities reported by college students are attention–deficit/hyperactivity disorder (ADHD) and learning disabilities (LD). Many questions remain regarding how best to support these students and whether services such as advising, coaching, and tutoring lead to significant academic gains. The current study examined the effect of support services on the GPA of students with LD and/or ADHD at a campus that specifically serves this population by tracking students’ support service usage and GPAs over a 5–year period. Results indicate that although most students who choose to receive coaching support experience academic gains, it is students with ADHD who obtain the greatest gains in GPA as a result of this support. Additionally, although tutoring can be of benefit to all students, significant GPA gains were obtained only for students with an LD diagnosis. Thus, there is a need to provide targeted supports aimed at addressing students’ specific areas of challenge.